IMPLEMENTASI KEBIJAKAN PNPM MANDIRI TAHUN 2010-2011 DI KELURAHAN MUGASARI - Dian Ristika; Endang Larasati; Margaretha Suryaningsih (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
National Community Empowerment Program is a national program of poverty reduction mainly based community empowerment. Indonesia has the problem of poverty and unemployment.Poverty in Indonesia can be seen from the three approaches, namely natural poverty, structural poverty, and the gap between region.Problem be triggered by low unemployment and employment opportunities for the labor force in urban.effort to mitigate them should use a multi-tiered approach discipline.Pemberdayaan proper dimension should incorporate aspects awareness aspects. National Program for Community Empowerment (PNPM Mandiri) empowerment-based course provides a space for people to be directly involved in addressing the problems of poverty, from the planning phase, the determination of the program, implementation, monitoring and evaluation. The general purpose of the National Program for Community Empowerment-Self is to improve the welfare and employment opportunities for the poor in mandiri.Dan specifically intended that the people in the village improvement program participants can enjoy the social, economic, and local governance.